Presence of Ruvettus pretiosus (Gempylidae) in the Colombian continental Caribbean - Gómez-Cubillos, María Camila; Programa de Biología Marina. Facultad de Ciencias Naturales e Ingeniería. Universidad de Bogotá Jorge Tadeo Lozano. Grupo de Investigación en Dinámica y Manejo de Ecosistemas Marino-Costeros DIMARCO. Carrera 2 No. 11-68 Edificio Mundo Marino, Rodadero, Santa Marta (Magdalena) Colombia. (2016)
The first record of Ruvettus pretiosus Cocco, 1833 for the Colombian continental Caribbean is presented. The specimen was collected at Los Cocos, department of Magdalena (11°16’33, 84’’ N 73°53’33, 01’’ W), using a demersal longline gear placed at 100 m depth. Biometrics, diagnosis and comments regarding its distribution, ecology and biology are included in the description. This new record expands the distribution of the species in the Caribbean Sea and increases the reported number of gempylids for Colombia to five.